ECOLOGICAL APPROACH ON SANITATION: COMPOSTING OF HUMAN EXCRETA USING BIOTOILET WITH LIGNOCELLULOSES WASTE MATERIAL AS MATRIX - Astuti, Jovita Tri; Nilawati, Dewi; Sintawardani, Neni (Bumi Lestari; Vol 17 No 1 (2017)DO - 10.24843/blje.2017.v17.i01.p05, 2017)
This study was aimed to evaluate the characteristic and prospect of lignocelluloses waste material, i.e. mixtured wood sawdust as matrix in composting human excreta using Biotoilet. Initially, 26.4 kg mixtured wood sawdust (+4/-32 mesh) moisture 11.84% was filled into Biotoilet chamber, and added with 20L tap water to achieve ±50% moisture. Mixer in Biotoilet was adjusted  to run-on intermittently with interval 15 min, each for 2 min, i.e. 1 min to clockwise and counter-clockwise, respectively. Exhaust fan with flow rate of 0.04m 3 .sec  was operated continuously to ensure proper aeration. Human excreta were loaded daily to Biotoilet chamber for 90 days which would be composted. Data showed that temperature of composting system was 25.70-43.67 -1 C. Moisture was 22.27-53.20% and pH 6.20-7.00. C/N ratio composted residual sawdust was 25:1. Ash, N, P, and K content were 11.78; 1.78; 0.85; and 0.95%, respectively. Bad odor was not created during composting. It was concluded mixtured wood sawdust could be used as matrix for composting human excreta. The compost could be categorized into Class-A that safe for food and non-food plant. Application of mixture wood sawdust as matrix in Biotoilet for composting human excreta could improve sanitation, prevent water degradation, at once increase soil quality for agricultural.